PELATIHAN COMUNICATION SKILL UNTUK MENUNJANG KEMAMPUAN TEKNIK PRESENTASI WARGA BELAJAR PKBM - Nika Sintesa; Yunita Indriany; Enny Dian Astuti; Sri Hastuti; Herry Syafrial (JURNAL ABDIMAS PLJ, 2023)
Students who study in non-formal education have the same opportunities in the world of work. The problem of the lack of information and skills that they have causes them to be less competitive in the world of work. Everyone, whether they realize it or not, will one day have the opportunity to speak. For many people, speaking in public is an extraordinary fear like being at the end of the age. Most people feel very nervous when speaking in public or as a public speaker. There are many things that must be mastered to be a good public speaker. Mastery of the material to be delivered, use of appropriate language and presentation methods, use of body language and vocal expressions and much more. In addition, mastery of the stage and practice are also things that must be learned. In order to prepare supplies to face the world of work, community service activities carried out by the Jakarta LP3I Polytechnic and attended by PKBM participants are in the form of Communication Skill Training with the Theme of Worryless Presentation Technique. With this training, it is hoped that it can provide knowledge and skills on how to present material through oral and written (slides), and can increase the confidence of the participants, especially in communicating in front of the public. Community Service Activities (P2M) are science and technology practices carried out by higher education institutions through the scientific method directly to the community outside the campus, especially in the context of transforming, developing, and disseminating science and technology. Overall, the Worry-Free Presentation Technique training activity in the communication process was considered successful. This success can be seen from the satisfaction of the participants after participating in the activity, interactive discussions and comments from the participants which were conveyed through messages after participating in this activity.Keywords : Communication Skills, Presentation Techniques, Public Speaking